Analisis Pengaruh CAR, NIM, LDR, Biaya Operasi, Size dan DPK Terhadap ROA (Studi Kasus pada Bank Umum Konvensional yang Terdaftar di BEI pada Periode 2010-2014) - Arumastuti, Nimas Kusudiatmi; Sampurno, R. Djoko (Diponegoro Journal of Management, 2016)
The purpose of this research is to examine the effects of Capital Adequacy Ratio, Net Interest Margin, Loan to Deposit Ratio, Operating Cost, Size and Third Party Funds on commercial banks profitability (ROA). This research uses data from the annual report published by banks, taken from Bloomberg and the official website of Indonesian Stock Exchange. Uses the purposive sampling method, samples for this research are 17 commercial banks with the amount of assets above 35 trillion. Data analysis method used in this research is multiple linear regression with panel data with significance level 5%. The result showed that CAR has negative relation and doesn’t significantly influences towards ROA. NIM has positive relation and significantly influence towards ROA. LDR and Operating Cost have negative relation and significantly influences towards ROA. Size and Third Party Funds have positive relation but don’t significantly influences to ROA. In this research, ROA could be explained by independent variables 72.8% whereas the rest explained by other variables which were not explained in this research.